The German book in Wolfenbüttel and abroad Studies presented to Ulrich Kopp in his retirement - Kelly, William A.; Beyer, Jürgen (Studies in Reading and Book Culture, 2014)
The texts assembled in this volume by a small body of scholars are a reflection of their respect and gratitude to Ulrich Kopp, who during his many years of service in Wolfenbüttel's Herzog August Bibliothek exhibited a variety of bibliographical expertise, which he was ever ready to put at their benefit. Contributors include Werner Arnold, Jürgen Beyer, Christoph and Gundula Boveland, Helmut Claus, John L. Flood, William A. Kelly, Robert Kolb, Hans-Jörg Künast, Gisela Möncke, Cornelia Niekus Moore, David Paisey, Christoph Reske, and Anne Simon.